Kandungan Total Fenolik dan Nilai Sun Protection Factor Ekstrak Sargassum sp. - Dimas Dharmawan; Norisca Aliza Putriana; Santi R. Anggraeni (Universitas Diponegoro, 2023)
Seaweed or macroalgae is one of the natural products with biological activities such as antioxidant, antibacterial, and immunostimulant. One of them is the brown alga Sargassum sp. This brown alga produces secondary metabolites such as flavonoids and their derivatives as well as polyphenols. These compounds have many roles in counteracting ultraviolet radiation and have the potential to be developed as active ingredients of sunscreen. This study aimed to determine the total phenolic content and the Sun Protection Factor (SPF) value of Sargassum sp. originating from Pameungpeuk beach, Garut Regency. The SPF value is used to categorize how efficiently a material prevents exposure to ultraviolet radiation. Total phenolic content was measured using Follin Ciocalteu reagent with gallic acid standard. The Sargassum sp extract sample contained total phenolic of 149,04±5,14 mg GAE/g. The SPF value of Sargassum sp extract was calculated using the Mansur equation at a wavelength of 290-320 nm. The obtained SPF value of extract was 33,2±3,11 which equals to oxybenzone. The value indicated an ultra-protection capability and the potency of extract for further development as UV filter. Rumput laut atau makroalga merupakan salah satu bahan alam dengan aktivitas biologis seperti antioksidan, aktivitas antibakteri dan imunostimulan. Salah satunya adalah alga cokelat jenis Sargassum sp. Alga cokelat ini menghasilkan metabolit sekunder seperti flavanoid dan turunannya serta polifenol dan turunannya. Senyawa-senyawa tersebut banyak berperan dalam menangkal radiasi ultraviolet dan berpotensi dikembangkan sebagai bahan aktif tabir surya. Penelitian ini bertujuan untuk mengetahui kandungan total fenolik dan nilai Sun Protection Factor (SPF) dari Sargassum sp yang berasal dari pantai Pameungpeuk, Kabupaten Garut. Kandungan total fenolik diukur dengan menggunakan reagen Follin Ciocalteu dan menggunakan standar baku asam galat. Sampel ekstrak Sargassum sp mengandung total fenolik sebesar 149,04±5,14 mg GAE/g. Nilai SPF digunakan untuk mengkategorikan seberapa efisien sebuah bahan dalam menangkal paparan radiasi sinar ultraviolet. Nilai SPF ekstrak Sargassum sp dihitung menggunakan menggunakan persamaan Mansur pada panjang gelombang 290-320 nm. Nilai SPF yang didapatkan yaitu 33,2±3,11 yang tergolong ke dalam kategori ultra.